The traitor's blade - Sands, Kevin (Sands, Kevin. Blackthorn key adventure, 2021)
In 1666, after four months away, friends Christopher Rowe, Tom, and Sally return to London triumphantly but, guided by coded riddles, face a conspiracy that threatens Christopher, as well as the King himself.